5 - Empowering Agricultural Labour in Ethiopia: The Challenges to Training and Development: par Kassa Belay - Belay, Kassa (Africa Development, 2000)
This paper reviews the historical development of agricultural education and training in Ethiopian institutions of higher learning. The review reveals that high level training in agriculture, which began in the early 1950s, has grown over the years. Today, the country has seven institutions of higher learning which train students in agriculture and related fields. The study shows that a host of factors, however, have put a stranglehold on the training process and the professional competence of agricultural graduates. Moreover, the results shed new light on the widening gap between the country's existing limited capacity to train agricultural labour and the ever increasing demand for highly skilled graduates in the sector. The study also reveals that the scarcity of highly qualified agricultural professionals, those with Bachelor's degree and above, has been accentuated and intensified through time.